Penerapan Prinsip HAM dalam Konteks Hukum dan Evaluasi Perlindungan di Berbagai Tingkatan Peradilan - Shilna Layinatul Latifah (ALADALAH: Jurnal Politik, Sosial, Hukum dan Humaniora, 2024)
This study examines the application of human rights principles within the legal context and evaluates protection at various judicial levels in Indonesia. Through comparative analysis and case studies, the article explores how HR principles are applied by district courts, high courts, and the Supreme Court. Additionally, this research identifies the main challenges in implementation and suggests steps to enhance HR protection within the judicial system. The findings indicate that despite significant efforts to integrate HR principles, structural and procedural obstacles still hinder their effective implementation